Metal micro-detectors: development of “transparent” position sensitive detector for beam diagnostics - O. Fedorovich, O. Kovalchuk, V. Pugatch, O. Okhrimenko, D. Storozhyk, V. Kyva (Вопросы атомной науки и техники, 2012)
Metal Micro-strip Detector (MMD) represents a novel position sensitive detector for wide range of applications. The main advantages of MMD are low thickness, high radiation resistance and high spatial resolution. MMD production technology includes some stages: micro-strip layout made by photo-lithography on silicon wafer, plasma-chemistry etching of the silicon wafer in the operating window, micro-cabling connection to the readout electronics and DAQ. Commercially available read-out systems (VA_SCM3 microchip preamplifier, Time Pix readout chip, Gotthard, X-DAS) have been studied for use with MMD. Characterization studies of the MMD are presented in details.